Negative electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

JP7668469B2Active Publication Date: 2025-04-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022512059
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-25
Publication Date
2025-04-25
Estimated Expiration
2041-03-25

AI Technical Summary

Technical Problem

Silicon-based negative electrode materials for secondary batteries experience large volume changes during lithium ion absorption and release, leading to conductive path breakdown and reduced cycle characteristics, while high carbon nanotube content improves conductivity but decreases initial discharge capacity.

Method used

A negative electrode mixture layer containing a combination of first and second lithium silicate phases with silicon particles, along with carbon nanotubes of small diameter (1-5 nm) to enhance lithium ion absorption and release, maintaining a conductive path and increasing initial discharge capacity.

Benefits of technology

The solution effectively increases the initial discharge capacity and improves cycle characteristics of secondary batteries by stabilizing the conductive path and reducing volume changes in silicon-based active materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000012_0000
    Figure 00000012_0000
Patent Text Reader

Abstract

This negative electrode for nonaqueous electrolyte secondary batteries is provided with a negative electrode mixture layer that contains a negative electrode active material and carbon nanotubes. The negative electrode active material contains a first negative electrode active material and a second negative electrode active material; the first negative electrode active material and the second negative electrode active material contain lithium silicate phases, each of which contains lithium, silicon and oxygen, and silicon particles that are dispersed in the lithium silicate phases; the molar ratios of oxygen to silicon (O / Si) in the lithium silicate phases are different from each other; the carbon nanotubes have a diameter of from 1 nm to 5 nm; and the ratio of the mass of the first negative electrode active material relative to the total mass of the first negative electrode active material and the second negative electrode active material is 60% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Negative electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

[0001] The present disclosure relates to a negative electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery.

[0002] Silicon-based materials, which can absorb and release more lithium ions than carbon materials such as graphite, have been investigated as negative electrode active materials for high-capacity secondary batteries. However, silicon-based materials undergo large volume changes associated with the absorption and release of lithium ions, which can lead to the disconnection of the conductive paths within the negative electrode mixture layer after repeated charge and discharge, resulting in a deterioration in the cycle characteristics of the secondary battery. Patent Document 1 discloses a secondary battery whose cycle characteristics are improved by incorporating carbon nanotubes of a specified size into the negative electrode mixture layer at a ratio of 0.1 to 2% by mass.

[0003] JP 2016-110876 A

[0004] The secondary battery disclosed in Patent Document 1 has a large diameter of carbon nanotubes in the negative electrode mixture layer and a high carbon nanotube content, so although the cycle characteristics are improved, the initial discharge capacity may decrease. Patent Document 1 does not consider achieving both the initial discharge capacity and the cycle characteristics, and there is still room for improvement.

[0005] A negative electrode for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector, the negative electrode mixture layer including a negative electrode active material and carbon nanotubes. The negative electrode active material includes a first negative electrode active material and a second negative electrode active material. The first negative electrode active material includes a first lithium silicate phase containing lithium, silicon, and oxygen, and first silicon particles dispersed in the first lithium silicate phase, where A1 indicating a molar ratio of oxygen to silicon (O / Si) in the first lithium silicate phase satisfies the relationship 2<A1≦3. The second negative electrode active material includes a second lithium silicate phase containing lithium, silicon, and oxygen, and second silicon particles dispersed in the second lithium silicate phase, where A2 indicating a molar ratio of oxygen to silicon (O / Si) in the second lithium silicate phase satisfies the relationship 3<A2≦4. The carbon nanotubes have a diameter of 1 nm to 5 nm. A ratio of the mass of the first negative electrode active material to the total mass of the first negative electrode active material and the second negative electrode active material is 60% or less.

[0006] A non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes the above-described negative electrode for a non-aqueous electrolyte secondary battery, a positive electrode containing a positive electrode active material, and a non-aqueous electrolyte.

[0007] According to one aspect of the present disclosure, it is possible to increase the initial discharge capacity of a secondary battery while improving its cycle characteristics.

[0008] FIG. 1 is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment of the present invention.

[0009] As described above, silicon-based materials are anode active materials that can increase the capacity of secondary batteries. However, due to their large volumetric change during charge and discharge, a decrease in discharge capacity due to charge and discharge cycling can be problematic. The method disclosed in Patent Document 1, in which a large amount of carbon nanotubes are incorporated into the anode mixture layer as a conductive additive to maintain a conductive path even after charge and discharge cycling, reduces the content of the anode active material in the anode mixture layer. This can improve cycle characteristics, but may result in a decrease in initial discharge capacity. Furthermore, as described in Patent Document 1, the anode mixture slurry may have poor dispersibility if it contains a large amount of large-diameter carbon nanotubes. On the other hand, among silicon-based materials, anode active materials containing silicon particles in a lithium silicate phase containing lithium, silicon, and oxygen can occlude and release many lithium ions, but they tend to crack during charge and discharge cycling, which makes them more susceptible to side reactions, such as reactions with the electrolyte, and can result in a decrease in cycle characteristics. Therefore, the inventors conducted extensive research to solve the above problems, and discovered that by preparing two types of particles containing a lithium silicate phase with silicon particles dispersed therein and mixing these in an appropriate ratio to form a negative electrode active material, and combining this with carbon nanotubes having a relatively small diameter, it is possible to specifically increase the initial discharge capacity of a secondary battery while improving its cycle characteristics.

[0010] An example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail below. Hereinafter, a cylindrical battery in which a wound electrode assembly is housed in a cylindrical exterior body will be exemplified. However, the electrode assembly is not limited to the wound type and may be a laminated type in which multiple positive electrodes and multiple negative electrodes are alternately stacked one by one with separators interposed therebetween. Furthermore, the exterior body is not limited to a cylindrical shape and may be, for example, prismatic or coin-shaped, or may be a battery case made of a laminate sheet including a metal layer and a resin layer.

[0011] Fig. 1 is a longitudinal cross-sectional view of a cylindrical secondary battery 10 according to an embodiment. The secondary battery 10 shown in Fig. 1 includes an electrode assembly 14 and a non-aqueous electrolyte housed in an exterior body 15. The electrode assembly 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. For ease of explanation, the following description will refer to the sealing body 16 side as the "top" and the bottom side of the exterior body 15 as the "bottom."

[0012] The upper open end of the exterior body 15 is closed with the sealing body 16, thereby sealing the interior of the secondary battery 10. Insulating plates 17 and 18 are provided above and below the electrode body 14. The positive electrode lead 19 extends upward through a through hole in the insulating plate 17 and is welded to the underside of a filter 22, which is the bottom plate of the sealing body 16. In the secondary battery 10, a cap 26, which is the top plate of the sealing body 16 and is electrically connected to the filter 22, serves as the positive electrode terminal. On the other hand, the negative electrode lead 20 passes outside the insulating plate 18, extends toward the bottom side of the exterior body 15, and is welded to the inner surface of the bottom of the exterior body 15. In the secondary battery 10, the exterior body 15 serves as the negative electrode terminal.

[0013] The exterior body 15 is, for example, a cylindrical metal exterior can with a bottom. A gasket 27 is provided between the exterior body 15 and the sealing body 16 to ensure the internal sealing of the secondary battery 10. The exterior body 15 has a grooved portion 21 that supports the sealing body 16, formed, for example, by pressing the side surface from the outside. The grooved portion 21 is preferably formed in an annular shape along the circumferential direction of the exterior body 15, and supports the sealing body 16 on its upper surface via the gasket 27.

[0014] The sealing body 16 includes a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cap 26, which are stacked in this order from the electrode body 14 side. Each component of the sealing body 16 has, for example, a disk or ring shape, and all components except for the insulating member 24 are electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective centers, with the insulating member 24 interposed between their respective peripheral edges. If the internal pressure of the battery increases due to abnormal heat generation, for example, the lower valve body 23 may rupture, causing the upper valve body 25 to bulge toward the cap 26 and separate from the lower valve body 25, thereby cutting off the electrical connection between them. If the internal pressure continues to increase, the upper valve body 25 may rupture, allowing gas to be released from the opening 26a of the cap 26.

[0015] The positive electrode 11, the negative electrode 12, the separator 13, and the non-aqueous electrolyte that constitute the secondary battery 10, and in particular the negative electrode mixture layer 41 that constitutes the negative electrode 12, will be described in detail below.

[0016] [Positive Electrode] The positive electrode 11 has a positive electrode current collector 30 and a positive electrode mixture layer 31 formed on the surface of the positive electrode current collector 30. The positive electrode current collector 30 can be a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, or a film with such a metal disposed on its surface. The positive electrode mixture layer 31 may contain a positive electrode active material, a binder, a conductive agent, etc. The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive agent, etc. to the surface of the positive electrode current collector 30, drying the coating, and then compressing it to form the positive electrode mixture layer 31 on both sides of the positive electrode current collector 30.

[0017] The positive electrode active material contained in the positive electrode mixture layer 31 may contain a lithium transition metal oxide as a main component. The positive electrode active material may be composed essentially of a lithium transition metal oxide alone, or may be a lithium transition metal oxide particle having inorganic compound particles or the like fixed to the surface thereof. One type of lithium transition metal oxide may be used, or two or more types may be used in combination.

[0018] Lithium transition metal oxides have the general formula Li a Ni x Co y M 1-x-y O 2―b(wherein 0.97≦a≦1.2, 0.8≦x≦1.0, 0≦y≦0.1, 0≦b<0.05, and M contains at least one element selected from Ca, Mn, Al, B, W, Sr, Mg, Mo, Nb, Ti, Si, and Zr).

[0019] Examples of the conductive agent contained in the positive electrode mixture layer 31 include carbon materials such as carbon black (CB), acetylene black (AB), ketjen black, carbon nanotubes, carbon nanofibers, and graphite. These may be used alone or in combination of two or more.

[0020] Examples of the binder contained in the positive electrode mixture layer 31 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resin, acrylic resin, polyolefin resin, etc. These may be used alone or in combination of two or more.

[0021] [Negative Electrode] The negative electrode 12 has a negative electrode current collector 40 and a negative electrode mixture layer 41 formed on the surface of the negative electrode current collector 40. The negative electrode current collector 40 can be a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a film with such a metal disposed on its surface. The negative electrode mixture layer 41 contains a negative electrode active material and carbon nanotubes. The negative electrode 12 can be produced, for example, by applying a negative electrode mixture slurry containing a negative electrode active material, carbon nanotubes, etc. to the surface of the negative electrode current collector 40, drying the coating, and then compressing it to form the negative electrode mixture layer 41 on both sides of the negative electrode current collector 40.

[0022] The diameter of the carbon nanotubes is 1 nm to 5 nm, preferably 1 nm to 3 nm. By using carbon nanotubes with such a relatively small diameter, a conductive path between the negative electrode active material can be ensured with a smaller content than when using carbon nanotubes with a larger diameter, and therefore the content of the negative electrode active material in the negative electrode mixture layer 41 can be increased. Furthermore, the use of such carbon nanotubes improves the dispersibility of the negative electrode mixture slurry. The carbon nanotubes contained in the negative electrode mixture layer 41 may be, for example, single-walled carbon nanotubes.

[0023] The length of the carbon nanotubes may be 5 μm or more, which increases the aspect ratio of the carbon nanotubes and improves the conductivity, thereby ensuring a conductive path between the negative electrode active materials with a smaller content.

[0024] In the negative electrode mixture layer 41, the mass ratio of the carbon nanotubes to the mass of the negative electrode active material may be 0.005% to 0.05%. If the mass ratio of the carbon nanotubes is 0.005% or more, a conductive path between the negative electrode active materials can be secured, thereby obtaining good cycle characteristics. If the mass ratio of the carbon nanotubes is 0.05% or less, an appropriate amount of negative electrode active material can be contained in the negative electrode mixture layer 41, which is advantageous from the viewpoint of discharge capacity.

[0025] The negative electrode mixture layer 41 may further contain a conductive additive other than carbon nanotubes. Examples of conductive additives other than carbon nanotubes include carbon black (CB), acetylene black (AB), ketjen black, and carbon nanofibers. These may be used alone or in combination of two or more. From the viewpoint of incorporating an appropriate amount of negative electrode active material into the negative electrode mixture layer 41, the total mass of the conductive additives including carbon nanotubes is preferably 0.05% or less with respect to the mass of the negative electrode active material.

[0026] The negative electrode mixture layer 41 may further contain a binder. As in the case of the positive electrode 11, the binder may be a fluororesin, PAN, polyimide resin, acrylic resin, polyolefin resin, or the like. These may be used alone or in combination of two or more. When preparing the negative electrode mixture slurry using an aqueous solvent, it is preferable to use carboxymethyl cellulose (CMC) or a salt thereof, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol, or the like in combination.

[0027] The negative electrode active material contained in the negative electrode mixture layer 41 includes a first negative electrode active material and a second negative electrode active material. Both the first negative electrode active material and the second negative electrode active material are particles having a volume-based median diameter (D50) of, for example, 1 μm to 25 μm, preferably 4 μm to 15 μm. The D50 value can be reduced by pulverizing the negative electrode active material with a ball mill. D50 refers to the particle size at which the cumulative frequency in the volume-based particle size distribution is 50% from the smallest particle size, and is also referred to as the median diameter. The particle size distribution of the negative electrode active material can be measured using a laser diffraction particle size distribution analyzer (e.g., LA-750 manufactured by Horiba, Ltd.) using water as a dispersion medium.

[0028] The first negative electrode active material includes a first lithium silicate phase containing lithium, silicon, and oxygen, and first silicon particles dispersed within the first lithium silicate phase. A1, which indicates the molar ratio of oxygen to silicon (O / Si) in the first lithium silicate phase, satisfies the relationship 2<A1≦3. Note that the first negative electrode active material may include phases other than the first lithium silicate phase as long as the object of the present disclosure is not impaired. However, in this embodiment, the first negative electrode active material includes only the first lithium silicate phase.

[0029] The first negative electrode active material may have a conductive layer covering at least a portion of the surface. The conductive layer contains a conductive material. This can improve the conductivity of the first negative electrode active material. For example, a carbon material can be used as the conductive material. The conductive layer can be thin enough not to affect the average particle size of the first negative electrode active material.

[0030] The first lithium silicate phase can be, for example, a compound having the general formula Li 2 Si x O 2x+1 (x≧1). From the viewpoint of the stability and lithium ion conductivity of the first lithium silicate phase, x preferably satisfies the relationship 1≦x≦2. Note that B1, which indicates the molar ratio of lithium to silicon (Li / Si) in the first lithium silicate phase, may satisfy the relationship 0<B1≦2 or may be 1≦B1≦2.

[0031] The first lithium silicate phase may further contain at least one element selected from the group consisting of Na, K, Mg, Ca, Ba, Zr, Nb, Ta, V, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, F, W, Al, La, and B. The content of these elements in the first lithium silicate phase is preferably such that it does not affect the discharge capacity, and may be, for example, a molar ratio of 0.01 or less relative to the total of Li, Si, and O in the first lithium silicate phase. The content of the above elements, such as Na, in the first lithium silicate phase can be measured by completely dissolving the negative electrode active material in hot hydrofluoric nitric acid (a mixed acid of heated hydrofluoric acid and nitric acid), filtering to remove carbon from the dissolved residue, and then analyzing the obtained filtrate by inductively coupled plasma atomic emission spectroscopy (ICP-AES).

[0032] The first silicon particles dispersed in the first lithium silicate phase suppress volumetric changes of the first negative electrode active material during charge and discharge. The first silicon particles may have a crystallite size of, for example, 10 nm or more. This reduces the surface area of ​​the first silicon particles, thereby suppressing deterioration of the first silicon particles. The crystallite size of the first silicon particles is calculated using the Scherrer equation from the half-width of the diffraction peak assigned to the Si(111) plane in the X-ray diffraction (XRD) pattern of the first silicon particles.

[0033] The first silicon particles are an aggregate of multiple crystallites. From the viewpoint of suppressing cracking of the first silicon particles, the average particle size of the first silicon particles before the first charge is preferably 500 nm or less, more preferably 200 nm or less, and particularly preferably 50 nm or less. After the first charge, the average particle size of the first silicon particles is preferably 400 nm or less, more preferably 100 nm or less. By miniaturizing the first silicon particles, volume change during charge and discharge can be further suppressed. The average particle size of the first silicon particles is determined by analyzing a cross-sectional SEM image obtained by observing a cross section of the first negative electrode active material with a scanning electron microscope (SEM). Specifically, the grain boundaries of 100 randomly selected primary particles from the cross-sectional SEM image are observed, the outer shapes of the primary particles are identified, and the major axis (longest diameter) of each of the 100 primary particles is determined, and the average value thereof is taken as the average particle size of the first silicon particles.

[0034] The content of the first silicon particles in the first negative electrode active material is, for example, preferably 30% by mass or more, more preferably 50% by mass or more, and particularly preferably 55% by mass or more in order to increase the diffusibility of lithium ions and thereby increase the capacity. On the other hand, the content of the first silicon particles in the first negative electrode active material is, for example, preferably 95% by mass or less, more preferably 80% by mass or less, and particularly preferably 75% by mass or less in order to suppress the reaction between the electrolyte solution and the first silicon particles by covering the surfaces of the first silicon particles with the first lithium silicate phase.

[0035] The content of the first silicon particles can be measured using Si-NMR (Varian, INOVA-400) under the following measurement conditions.

[0036] Probe: Varian 7 mm CPMAS-2 MAS: 4.2 kHz MAS speed: 4 kHz Pulse: DD (45° pulse + signal acquisition time 1 H decoupled) Repetition time: 1200 sec Observation width: 100 kHz Observation center: around -100 ppm Signal acquisition time: 0.05 sec Number of accumulations: 560 Sample amount: 207.6 mg First lithium silicate phase Li 2 Si x O 2x+1The composition (x≧1) can be analyzed, for example, by the following method. The following describes the case where the first lithium silicate phase does not contain elements such as Na. However, if elements such as Na are contained, the contents of these elements are subtracted beforehand in the calculation. (1) The mass of a sample of the first negative electrode active material is measured. (2) The contents of carbon, oxygen, and lithium contained in the sample are calculated as follows. (3) The carbon content and silicon content are subtracted from the mass of the sample to calculate the contents of lithium and oxygen in the remaining amount, and the ratio of 2 to (2x+1) is found from the molar ratio of lithium to oxygen to calculate x.

[0037] The carbon content of the sample can be measured using a carbon / sulfur analyzer (EMIA-520 model manufactured by Horiba, Ltd.). The sample is weighed onto a magnetic board, a combustion improver is added, and the board is inserted into a combustion furnace (carrier gas: oxygen) heated to 1350°C, and the amount of carbon dioxide gas generated during combustion is detected by infrared absorption. For example, a calibration curve is created using carbon steel (carbon content 0.49%) manufactured by Bureau of Analyzed Sampels Ltd., and the carbon content of the sample is calculated. The carbon content of the sample is mainly derived from the conductive layer.

[0038] The oxygen content of the sample can be measured using an oxygen, nitrogen, and hydrogen analyzer (EGMA-830 model manufactured by Horiba, Ltd.). The sample is placed in a Ni capsule, and then placed in a carbon crucible heated at 5.75 kW with Sn pellets and Ni pellets as flux, and the released carbon monoxide gas is detected. Standard Sample Y 2 O 3 A calibration curve is created using the above formula and the oxygen content of the sample is calculated.

[0039] The lithium content of a sample can be measured by completely dissolving the sample in hot fluoronitric acid (a mixture of heated hydrofluoric acid and nitric acid), filtering to remove the carbon residue, and then analyzing the resulting filtrate with inductively coupled plasma atomic emission spectroscopy (ICP-AES). A calibration curve is created using a commercially available standard solution, and the lithium content of the sample is calculated.

[0040] The silicon content of the sample is the mass of the first negative electrode active material minus the carbon content, oxygen content, and lithium content. This silicon content includes both silicon present in the form of silicon particles and silicon present in the form of lithium silicate. The content of silicon present in the form of lithium silicate can be determined by subtracting the content of silicon particles determined by the Si-NMR measurement from this silicon content.

[0041] The second negative electrode active material includes a second lithium silicate phase containing lithium, silicon, and oxygen, and second silicon particles dispersed within the second lithium silicate phase. A2, which indicates the molar ratio of oxygen to silicon (O / Si) in the second lithium silicate phase, satisfies the relationship 3<A2≦4. The second negative electrode active material may include a phase other than the second lithium silicate phase as long as the objectives of the present disclosure are not impaired. However, in this embodiment, the second negative electrode active material includes only the second lithium silicate phase. The second negative electrode active material may have a conductive layer containing a conductive material such as a carbon material, covering at least a portion of its surface. The conductive layer may be thin enough not to affect the average particle size of the second negative electrode active material.

[0042] The second lithium silicate phase can be, for example, of the general formula Li 2 Si y O 2y+1 (y<1). Preferably, y satisfies the relationship 0.5≦y<1. Note that B2, which indicates the molar ratio of lithium to silicon (Li / Si) in the second lithium silicate phase, may satisfy the relationship 2<B2≦4. Furthermore, the second lithium silicate phase may contain trace amounts of elements such as Na, which are exemplified for the first lithium silicate phase, in addition to lithium, silicon, and oxygen.

[0043] The second silicon particles dispersed in the second lithium silicate phase suppress volumetric changes of the second negative electrode active material during charge and discharge. The second silicon particles may have a crystallite size of, for example, 10 nm or more. The second silicon particles are aggregates of a plurality of crystallites. From the viewpoint of suppressing cracking of the second silicon particles, the average particle size of the second silicon particles before the first charge is preferably 500 nm or less, more preferably 200 nm or less, and particularly preferably 50 nm or less. After the first charge, the average particle size of the second silicon particles is preferably 400 nm or less, more preferably 100 nm or less.

[0044] The lower limit of the content of the second silicon particles in the second negative electrode active material is, for example, preferably 30% by mass, more preferably 50% by mass, and particularly preferably 55% by mass, from the viewpoint of increasing capacity. The upper limit of the content of the first silicon particles in the first negative electrode active material is, for example, preferably 95% by mass, more preferably 80% by mass, and particularly preferably 75% by mass, from the viewpoint of suppressing side reactions. The content of the second silicon particles can be measured in the same manner as the content of the first silicon particles. The composition of the second lithium silicate phase can also be calculated in the same manner as the composition of the first lithium silicate phase.

[0045] Before the first charge, the second negative electrode active material may contain a precursor of the second negative electrode active material. The composition of the precursor of the second negative electrode active material may be, for example, SiO z (0.5≦Z≦1.5). z is SiO 2 phase and SiO 2 The first charge may contain silicon particles dispersed within the SiO 2 The lithium silicate phase absorbs lithium ions to form a second lithium silicate phase. 4 SiO 4 This forms a second negative electrode active material including a second lithium silicate phase and second silicon particles dispersed in the second lithium silicate phase.

[0046] The mass ratio of the first negative electrode active material to the total mass of the first negative electrode active material and the second negative electrode active material may be 60% or less, more preferably 20% or less. Mixing two types of negative electrode active materials can increase the initial discharge capacity of the secondary battery while improving its cycle characteristics. Because the first negative electrode active material and the second negative electrode active material absorb and release lithium ions at different times during charging and discharging, mixing these two types of negative electrode active materials in an appropriate ratio can achieve the above-mentioned effects. Furthermore, because the first negative electrode active material and the second negative electrode active material also differ in hardness, mixing them in the above-mentioned ratio can favorably maintain a conductive path between the negative electrode active materials.

[0047] In addition to the first and second negative electrode active materials, the negative electrode active material may include a third negative electrode active material, such as a carbon material capable of absorbing and releasing lithium ions, such as graphite (natural graphite or artificial graphite), a metal that alloys with lithium, such as tin, a metal compound containing tin, or a non-carbon material, such as a lithium-titanium composite oxide. Graphite is preferred as the third negative electrode active material because it exhibits small volume changes during charge and discharge. The proportion of the third negative electrode active material in the total negative electrode active material may be, for example, 80% to 95% by mass. This range can mitigate the volume changes of the silicon-based negative electrode active material during charge and discharge, improving cycle characteristics.

[0048] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous membrane, a woven fabric, and a nonwoven fabric. Suitable materials for the separator 13 include olefin resins such as polyethylene and polypropylene, and cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer containing a heat-resistant material may be formed on the surface of the separator 13. Examples of heat-resistant materials include polyamide resins such as aliphatic polyamides and aromatic polyamides (aramids), and polyimide resins such as polyamideimides and polyimides.

[0049] [Non-aqueous electrolyte] As the non-aqueous solvent (organic solvent) of the non-aqueous electrolyte, carbonates, lactones, ethers, ketones, esters, etc. can be used, and these solvents can be used in combination of two or more. As the electrolyte salt of the non-aqueous electrolyte, LiPF 6 , LiBF 4 , LiCF 3 SO 3 The amount of electrolyte salt dissolved in the non-aqueous solvent can be, for example, 0.5 to 2.0 mol / L.

[0050] <Examples> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.

[0051] Example 1 Synthesis of First Negative Electrode Active Material Silicon dioxide and lithium carbonate were mixed so that the molar ratio of Si / Li was 1.05, and the mixture was baked in air at 950° C. for 10 hours to obtain a first negative electrode active material. 2 Si 2 O 5 The lithium silicate thus obtained was pulverized to an average particle size of 10 μm. 2 Si 2 O 5 and raw material silicon (3N, average particle size 10 μm) were mixed in a mass ratio of 45:55, and this mixture was charged into a pot (made of SUS, volume: 500 mL) of a planetary ball mill (manufactured by Fritsch, P-5). 24 SUS balls (diameter 20 mm) were placed in the pot, the pot was closed with a lid, and the mixture was ground at 200 rpm for 50 hours in an inert atmosphere.

[0052] Next, the pulverized powder mixture was removed and fired at 800°C for 4 hours in an inert atmosphere with pressure applied by a hot press to obtain a sintered body of the mixture. The sintered body was then pulverized, passed through a 40 μm mesh, and mixed with coal pitch (MCP250, manufactured by JFE Chemical Corporation). The mixture was fired at 800°C in an inert atmosphere to coat the surface with conductive carbon to form a conductive layer. The coating amount of the conductive layer was 5% by mass relative to the mass of the first negative electrode active material. The mixture was then sieved to obtain a first negative electrode active material with an average particle size of 5 μm and a conductive layer on its surface.

[0053] The crystallite size of the silicon particles of the first negative electrode active material was 15 nm. In the first lithium silicate phase, the O / Si ratio was 2.5 and the Si / Li ratio was 1.0. In the first negative electrode active material, the first lithium silicate phase Li 2 Si 2 O 5 The content of silicon particles was 45 mass %, and the content of silicon particles was 55 mass %. The first negative electrode active material did not contain elements such as Na.

[0054] [Preparation of Precursor of Second Negative Electrode Active Material] SiO 2 SiO particles (average particle size 5 μm) with silicon particles dispersed therein were mixed with coal pitch (MCP250, manufactured by JFE Chemical Corporation), and the mixture was fired at 800°C in an inert atmosphere to coat the surfaces of the SiO particles with conductive carbon to form a conductive layer. The amount of the conductive layer coated was 5 mass% based on the total mass of the SiO particles and the conductive layer. In this way, SiO particles (precursors of the second negative electrode active material) with an average particle size of 5 μm and having a conductive layer on their surfaces were obtained.

[0055] The first charge causes the SiO particles to 2 The phase is mainly a secondary lithium silicate phase Li 4 SiO 4 The precursor is Li 4 SiO 4 and Li 4 SiO 4 The second negative electrode active material contains silicon particles dispersed therein. 4 SiO 4The content of silicon particles absorbing lithium ions was 42% by mass, and the content of silicon particles absorbing lithium ions was 58% by mass. The content of silicon particles excluding the lithium ions absorbed therein was 29% by mass. The first negative electrode active material did not contain elements such as Na.

[0056] [Preparation of Negative Electrode] A mixed negative electrode active material was obtained by mixing 1 part by mass of the first negative electrode active material, 4 parts by mass of the precursor of the second negative electrode active material, and 95 parts by mass of graphite as the third negative electrode active material. Next, this mixed negative electrode active material, carbon nanotubes having a diameter of 1.2 to 2 nm, an average diameter of 1.6 nm, and a length of 5 μm, styrene-butadiene rubber (SBR), and carboxymethyl cellulose sodium (CMC-Na) were prepared in a mass ratio of 100:0.01:1:1, and then kneaded with an N-methyl-2-pyrrolidone (NMP) solution to prepare a negative electrode mixture slurry. The negative electrode mixture slurry was applied to a copper negative electrode current collector, the coating was dried, and then the coating was rolled using a roller and cut to a predetermined electrode size, resulting in a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode current collector.

[0057] [Preparation of Positive Electrode] Lithium nickel composite oxide (LiNi 0.8 Co 0.18 Al 0.02 ) was used as the positive electrode active material. This positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a solids mass ratio of 95:2.5:2.5, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added. The mixture was then kneaded to prepare a positive electrode mixture slurry. The positive electrode mixture slurry was applied to both sides of an aluminum positive electrode current collector, and the coating was dried. The coating was then rolled using a roller and cut to a predetermined electrode size, yielding a positive electrode in which a positive electrode mixture layer was formed on both sides of the positive electrode current collector.

[0058] [Preparation of non-aqueous electrolyte] A non-aqueous solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 1:3, and LiPF 6 as an electrolyte salt was added to the non-aqueous solvent. 6 was dissolved at 1.0 mol / L to prepare a non-aqueous electrolyte solution, which was a liquid non-aqueous electrolyte.

[0059] [Battery Fabrication] An aluminum lead was attached to the positive electrode, and a nickel lead was attached to the negative electrode. The positive and negative electrodes were spirally wound with a polyolefin separator interposed therebetween, and then pressed radially to form a flat wound electrode assembly. This electrode assembly was housed in an exterior body made of an aluminum laminate sheet, and after the nonaqueous electrolyte was poured into it, the opening of the exterior body was sealed to obtain a battery for evaluation.

[0060] Example 2 A battery was fabricated in the same manner as in Example 1, except that in the fabrication of the negative electrode, 3 parts by mass of a first negative electrode active material, 3 parts by mass of a precursor of a second negative electrode active material, and 94 parts by mass of graphite as a third negative electrode active material were mixed to obtain a mixed negative electrode active material.

[0061] Example 3 A battery was fabricated in the same manner as in Example 1, except that in the fabrication of the negative electrode, 6 parts by mass of the first negative electrode active material, 4 parts by mass of a precursor of the second negative electrode active material, and 90 parts by mass of graphite as the third negative electrode active material were mixed to obtain a mixed negative electrode active material.

[0062] <Comparative Example 1> A battery was produced in the same manner as in Example 1, except that in producing the negative electrode, 4.5 parts by mass of the first negative electrode active material, 2.5 parts by mass of a precursor of the second negative electrode active material, and 93 parts by mass of graphite as the third negative electrode active material were mixed to obtain a mixed negative electrode active material.

[0063] <Comparative Example 2> A battery was produced in the same manner as in Example 1, except that in producing the negative electrode, 4 parts by mass of a precursor of the second negative electrode active material and 96 parts by mass of graphite as the third negative electrode active material were mixed to obtain a mixed negative electrode active material.

[0064] The initial discharge capacity and capacity retention rate of each of the above batteries were evaluated by the following method. The initial discharge capacity is shown as a relative value when the value of Comparative Example 1 is set to 100. The capacity retention rate is shown as a relative value when the value of Comparative Example 2 is set to 1. The batteries of the Examples and Comparative Examples were evaluated by the product of the initial discharge capacity and the capacity retention rate. Table 1 shows the evaluation results, as well as the contents of each of the first and second negative electrode active materials and the ratio of the mass of the first negative electrode active material to the total mass of the first and second negative electrode active materials.

[0065] [Measurement of initial discharge capacity] The batteries of the examples and comparative examples were charged at a constant current of 0.05 C in a temperature environment of 25° C. until the battery voltage reached 0 V, and then discharged at a constant current of 0.05 C until the battery voltage reached 1 V, and the initial discharge capacity was measured. 2 This refers to discharge in a battery in which a commonly used positive electrode, such as a lithium ion battery, is combined with a negative electrode. The batteries in the Examples and Comparative Examples use a negative electrode as the working electrode and metallic lithium (Li) as the counter electrode, so they should be called charging, but in accordance with the charge and discharge behavior of the negative electrode in a battery in which a commonly used positive electrode and negative electrode are combined, the charge and discharge directions are expressed in the opposite direction. In other words, charging is the flow of current to lower the potential of the negative electrode, which is the working electrode, and discharging is the flow of current to raise the potential of the negative electrode, which is the working electrode.

[0066] [Evaluation of Capacity Retention Rate After Cycle Test] The following cycle test was carried out on the battery in the initial state described above. The discharge capacity at the first cycle and the discharge capacity at the 300th cycle of the cycle test were determined, and the capacity retention rate was calculated according to the following formula.

[0067] Capacity retention rate (%) = (discharge capacity at 300th cycle / discharge capacity at 1st cycle) × 100 <Cycle test> First, the battery in an initial state was charged at a constant current of 0.05 C in a temperature environment of 25° C. until the battery voltage reached the set voltage of 0 V, and then discharged at a constant current of 0.05 C until the battery voltage reached 1 V. This charge-discharge cycle was repeated 300 times.

[0068]

[0069] As shown in Table 1, the batteries of the Examples had a larger value for the product of the initial discharge capacity and the capacity retention rate than the batteries of the Comparative Examples, and were found to be superior overall. The first negative electrode active material has a high capacity, but the capacity retention rate tends to decrease as the content increases. However, Example 1 achieved a capacity retention rate equivalent to that of Comparative Example 2, and it is presumed that the capacity retention rate is almost constant and the cycle characteristics are excellent when the ratio of the mass of the first negative electrode active material to the total mass of the first negative electrode active material and the second negative electrode active material is 20% or less.

[0070] REFERENCE SIGNS LIST 10 Secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Exterior body 16 Sealing body 17, 18 Insulating plate 19 Positive electrode lead 20 Negative electrode lead 21 Grooved portion 22 Filter 23 Lower valve body 24 Insulating member 25 Upper valve body 26 Cap 26a Opening 27 Gasket 30 Positive electrode current collector 31 Positive electrode mixture layer 40 Negative electrode current collector 41 Negative electrode mixture layer

Claims

1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector and containing a negative electrode active material and carbon nanotubes, wherein the negative electrode active material includes a first negative electrode active material and a second negative electrode active material, the first negative electrode active material includes a first lithium silicate phase containing lithium, silicon, and oxygen, and first silicon particles dispersed in the first lithium silicate phase, and A1 representing the molar ratio (O / Si) of oxygen to silicon in the first lithium silicate phase satisfies the relationship of 2 < A1 ≤ 3, the second negative electrode active material includes a second lithium silicate phase containing lithium, silicon, and oxygen, and second silicon particles dispersed in the second lithium silicate phase, and A2 representing the molar ratio (O / Si) of oxygen to silicon in the second lithium silicate phase satisfies the relationship of 3 < A2 ≤ 4, the diameter of the carbon nanotubes is 1 nm to 5 nm, and the ratio of the mass of the first negative electrode active material to the total mass of the first negative electrode active material and the second negative electrode active material is 60% or less.

2. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the ratio of the mass of the first negative electrode active material to the total mass of the first negative electrode active material and the second negative electrode active material is 20% or less.

3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein the first lithium silicate phase further contains at least one element selected from the group consisting of Na, K, Mg, Ca, Ba, Zr, Nb, Ta, V, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, F, W, Al, La, and B.

4. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein in the negative electrode mixture layer, the ratio of the mass of the carbon nanotubes to the mass of the negative electrode active material is 0.005% to 0.05%.

5. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein the length of the carbon nanotubes is 5 µm or more.

6. A non-aqueous electrolyte secondary battery comprising the negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5, a positive electrode containing a positive electrode active material, and a non-aqueous electrolyte.

7. The positive electrode active material is a general formula Li a Ni x Co y M 1-x-y O 2―b (wherein, 0.97 ≤ a ≤ 1.2, 0.8 ≤ x ≤ 1.0, 0 ≤ y ≤ 0.1, 0 ≤ b < 0.05, M contains at least one element selected from Ca, Mn, Al, B, W, Sr, Mg, Mo, Nb, Ti, Si, and Zr), and the non-aqueous electrolyte secondary battery according to claim 6.